Implementasi Pendidikan Multikultural dalam Membentuk Karakter Anak Usia Dini - Uswatun Hasanah (Pusat Penerbitan Universitas (P2U) Unisba, 2018)
AbstractThe purpose of this study was to reveal the implementation of multicultural education in shaping the character of early childhood at the Builder State Kindergarten in the District of Trimurjo, Central Lampung Regency. This research method is qualitative naturalistic. The results of this study, including through 3 parts, namely: 1) self-development program, 2) integration in subjects; 3) school culture. First, self-development programs, there are four activities, namely: routine activities, spontaneous activities, exemplary, conditioning. Second, integration in subjects. Educators teach multicultural education in the learning material. Third, school culture. Supporting factors for multicultural education include the presence of extra-curricular activities. While the inhibiting factors for multicultural education in Pembina Trimurjo State Kindergarten are: (1) Lack of understanding of educators about multicultural education; (2) The absence of a standard concept from the government regarding multicultural education related to the curriculum and methods.Keywords: Multicultural Education, Character, Early Childhood. AbstrakTujuan dari penelitian ini adalah mengungkap implementasi pendidikan multikultural dalam membentuk karakter anak usia dini di TK Negeri Pembina Kecamatan Trimurjo Kabupaten Lampung Tengah. Metode penelitian ini adalah kualitatif yang bersifat naturalistik. Hasil penelitian ini, di antaranya melalui 3 bagian yaitu: 1) program pengembangan diri, 2) pengintegrasian dalam mata pelajaran; 3) budaya sekolah. Pertama, program pengembangan diri, terdapat empat kegiatan yaitu: kegiatan rutin, kegiatan spontan, keteladanan, pengkondisian. Kedua, pengintegrasian dalam mata pelajaran. Pendidik mengajarkan pendidikan multikultural yang ada dalam materi pembelajaran. Ketiga, budaya sekolah. Faktor penunjang pendidikan multikultural di antaranya yaitu: adanya kegiatan ekstra kurikuler. Sedangkan faktor penghambat pendidikan multikultural di TK Negeri Pembina Trimurjo adalah: (1) Kurangnya pemahaman pendidik tentang pendidikan multikultural; (2) Belum adanya konsep baku dari pemerintah tentang pendidikan multikultural terkait kurikulum dan metodenya. Kata Kunci: Pendidikan Multikultural, Karakter, Anak Usia Dini.